Energy conservation and solar energy use for cooking impact of its massive adoption in the arid zone of Argentina - Esteves Miramont, Alfredo (2014)
The use of solar energy is essential in transforming today's human environments into tomorrow's sustainable human habitats. This paper presents the positive impacts produced by the adoption of energy-efficient cooking equipment-using heat retention box cookers and the solar drum ovens-in the arid zone of Argentine. These solar cooking technologies improve the quality of life for local populations and, at the same time, save energy, time and effort in trying to obtain firewood. They minimize serious health problems associated with greenhouse gas (GHG) emissions control. The study documental in this paper demonstrates that usage of these technologies results in the saving of 65.7% of Liquefied Petroleum Gas and 63.8% of Firewood utilized in Argentina's rural and arid zone. These results indicate that, if 50% of the arid zone population were to adopt these technologies, a reduction of 3.09KgCO2e of greenhouse gases per capita from 2015 to 2050 is possible.